2018
DOI: 10.1097/qad.0000000000001710
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure prophylaxis guidelines have low sensitivity for identifying seroconverters in a sample of young Black MSM in Chicago

Abstract: Low sensitivity of CDC guidelines and limited AUC of HIRI-MSM and Gilead screening tools are of concern for PrEP implementation among most at risk populations such as YBMSM. Consideration of demographics, local epidemiology, and network factors may better guide identification of clients who could benefit most from PrEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…Stigma reinforced by the association of PrEP with risky behaviour contributed to the decision of several of the participants to stop PrEP. Unfortunately, for many populations, HIV risk is driven not by behaviour but by one’s sexual network and/or one’s partners’ sexual network [42,43]. For this reason and others, the CDC guidelines predict HIV risk poorly among key populations such as black MSM and heterosexual women [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma reinforced by the association of PrEP with risky behaviour contributed to the decision of several of the participants to stop PrEP. Unfortunately, for many populations, HIV risk is driven not by behaviour but by one’s sexual network and/or one’s partners’ sexual network [42,43]. For this reason and others, the CDC guidelines predict HIV risk poorly among key populations such as black MSM and heterosexual women [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, for many populations, HIV risk is driven not by behaviour but by one’s sexual network and/or one’s partners’ sexual network [42,43]. For this reason and others, the CDC guidelines predict HIV risk poorly among key populations such as black MSM and heterosexual women [42,43]. In addition to removing barriers to PrEP delivery, PrEP should be normalized as a routine preventive health procedure for people potentially exposed to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…PrEP is recommended for populations with an HIV incidence above 2% per year (evidence rating AIII) and for HIV-seronegative partners of HIV-infected persons who are not consistently virally suppressed. 127,128 Unlike condoms, PrEP does not prevent other STIs. For people who inject drugs, clean injection equipment and access to substance use treatment should be available.…”
Section: Preventionmentioning
confidence: 99%
“…Several factors have been shown to limit PrEP uptake among YBMSM. They include decreased access and involvement with the health care system, low rates of providers prescribing PrEP (Eaton et al, 2015;Getting to Zero Illinois, 2019;Lancki, Almirol, Alon, McNulty, & Schneider, 2018), lack of PrEP awareness, perceived impact of side effects, and perceived inability to pay for PrEP, along with social barriers such as stigma around PrEP (Getting to Zero Illinois, 2019). Some of these barriers may be due to the disconnect between the CDC's PrEP guidelines and YBMSM.…”
mentioning
confidence: 99%
“…Some of these barriers may be due to the disconnect between the CDC's PrEP guidelines and YBMSM. One study showed that nearly half of Black gay, and bisexual men and other men who have sex with men (BMSM) who seroconverted did not meet CDC's PrEP eligibility criteria (Lancki et al, 2018). This is concerning because BMSM are reported to be equally or more willing to utilize PrEP for HIV prevention than their White counterparts (Lelutiu-Weinberger & Golub, 2016).…”
mentioning
confidence: 99%